The impact of the professional doctorate on managers' professional practice. Issue 1 (March 2021) - Creaton, Jane; Anderson, Valerie
Abstract: This paper contributes a new perspective on the impact of professional doctorates. Professional doctorates offer a form of higher-level management education, which aims to contribute to professional practice as well as to academic knowledge. Although there is a growing literature identifying the personal benefits of undertaking a professional doctorate, the evidence of wider impact on the workplace remains limited. Drawing on interviews with 25 professional doctorate graduates working in managerial and professional roles in different parts of the criminal justice sector, this study explores the wider impact of the professional doctorate. The paper identifies impact dimensions, influencers and processes. It extends the processual approach by conceptualizing impact as an active and negotiated process operating over time and in changing contexts. The analysis shows impact construction to be a complex and nuanced process, involving interactions between graduates and significant others beyond the realm of the university. The analysis has important implications for the design and delivery of professional doctorate programmes in management and business and for extended engagement by educators, professional bodies and employers with the issues of impact. Highlights: Achieving organizational impact from professional doctorate programmes is a complex and nuanced process. Doctoral impact is socially constructed through negotiation between student, employer and professional networks. Professional doctorate educators must encourage impact through graduates' situated practice outside the academy.